IMPLEMENTATION OF ONLINE SERVICE APPLICATION FOR POPULATION ADMINISTRATION REGISTRATION AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION - Fitri, Indie Nurul; Tukiman, (Jurnal Governansi, 2025)
The urgency of this research lies in evaluating the effectiveness of implementing the Online Population Administration Service (Poedak) application, developed by the Gresik District Office of Population and Civil Registration, as part of an e-government initiative to streamline population administration for the public. E-government refers to using information and communication technology to enhance public services, efficiency, and transparency in government administration. This study aims to assess the application of Poedak, identify obstacles hindering its implementation, and provide recommendations for improvement. The research employs a descriptive qualitative design with data collection techniques, including observation, interviews, documentation, and data analysis using Miles and Huberman’s interactive model. The findings indicate that the implementation of the Poedak application is not yet fully optimal. Major obstacles include insufficient outreach, which leads many citizens to prefer direct administration handling, and limited resources, such as staff and facilities, affecting service effectiveness. However, disposition and bureaucratic structure factors show good performance, with employees understanding the application and clear Standard Operating Procedures (SOPs). This study highlights the need for improved responses to complaints and expanded outreach to enhance the effectiveness and efficiency of Poedak implementation. The novelty of this research lies in its in-depth analysis of specific challenges in implementing digital administrative applications at the local level, along with practical recommendations for improving technology-based population administration systems.